2007
DOI: 10.1093/ps/86.5.999
|View full text |Cite
|
Sign up to set email alerts
|

Pathophysiology of Heart Failure in Broiler Chickens: Structural, Biochemical, and Molecular Characteristics

Abstract: Modern strains of fast-growing meat type poultry are highly susceptible to heart failure. Heart-related mortalities are observed predominantly in fast-growing broiler chickens, with ascites and sudden death syndrome being the most common heart-related conditions in modern broiler flocks. This paper examines the role of structural, molecular, and biochemical factors pertinent to the pathophysiology of heart failure in fast-growing broilers. Evidence explaining the pathogenesis of acute and chronic heart failure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

8
58
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(68 citation statements)
references
References 38 publications
8
58
0
2
Order By: Relevance
“…Frequently, birds which die of SDS to be in good condition without any discernible preexisting clinical signs and all birds were well-fleshed and had general pulmonary congestion (Olkowski, 2007). However, birds with history of cardiac rhythm disturbances and showing serious ventricular arrhythmia are at high risk of sudden death.…”
Section: Introductionmentioning
confidence: 99%
“…Frequently, birds which die of SDS to be in good condition without any discernible preexisting clinical signs and all birds were well-fleshed and had general pulmonary congestion (Olkowski, 2007). However, birds with history of cardiac rhythm disturbances and showing serious ventricular arrhythmia are at high risk of sudden death.…”
Section: Introductionmentioning
confidence: 99%
“…Cardiovascular disease is common in broilers during rearing and makes a significant contribution to mortality during rearing (Julian 2005;Olkowski 2007). Kittelsen et al (2015a) identified that 36% of the mortalities that occurred during the 3 days before transport could be attributed to sudden death syndrome, 18% to ascites, and 28% to endocarditis.…”
mentioning
confidence: 99%
“…Kittelsen et al (2015a) identified that 36% of the mortalities that occurred during the 3 days before transport could be attributed to sudden death syndrome, 18% to ascites, and 28% to endocarditis. Sudden death syndrome is thought to arise from acute heart failure following ventricular arrhythmias that can be precipitated by stressors (Olkowski 2007;Olkowski et al 2008). In Norway, in 2012/2013, postmortem examinations of broilers that (a) died in the barn within 3 days of transportation to slaughter and (b) were DOA at the processing plant (Kittelsen et al 2015a) showed that lung congestion in DOAs (57% of DOAs) was more prevalent than in broilers that died on the farm (38% of the deaths on-farm during the 3 days before transport).…”
mentioning
confidence: 99%
“…El síndrome de hipertensión pulmonar (SHP) ha sido atribuido a una insuficiente capacidad vascular pulmonar (Wang et al, 2002;Rabie et al, 2005) y a un limitado desarrollo cardiaco en estirpes de rápido crecimiento (Olkowski, 2007). Sin embargo estudios de fisiopatología (Burton y Smith, 1967;Pan et al, 2005;Cueva et al, 1974;Hernández, 1982) y expresión del RNA mensajero de los genes endotelina uno (ET1), adrenomedulina (Gómez et al, 2007), síntesis de óxido nítrico sintasa tres (NOS3) (Moreno de Sandino, 2004;Gómez, 2008), sugieren que existe un factor genético relacionado con la susceptibilidad a desarrollar SHP en pollos de engorde sometidos a hipoxia hipobárica crónica o a bajas temperaturas.…”
Section: Introductionunclassified